Cross-Disciplinary Research on Learning and Instruction – Coming to Terms - Heitzmann, Nicole; Opitz, Ansgar; Stadler, Matthias; Sommerhoff, Daniel; Fink, Maximilian C.; Obersteiner, Andreas; Schmidmaier, Ralf; Neuhaus, Birgit J.; Ufer, Stefan; Seidel, Tina; Fischer, Martin R.; Fischer, Frank (Frontiers in Psychology, 2021)
no abstract for opinion paper